Eksistensi Pemahaman Ayat Al-Qur’an dan Pengaruhnya terhadap Jiwa Mahasiswa Kampus 2 IAIN Sultan Amai Gorontalo - Masyita Djauhari; Mustaqimah Mustaqimah; Indra Dewi Seri Yusuf (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
The main study that will be discussed in this research is how the existence of understanding the verses of the Qur'an and its influence on the souls of the students of IAIN Sultan Amai Gorontalo campus 2 are and what are the obstacles and solutions for students who are not influenced by the Qur’an. In this study, the author uses a qualitative research type, namely field research using an interpretive approach, using the mauḍū’i method. The method that the author uses generally uses the following steps: defining the problem to be discussed (topic); collect verses related to the problem; arrange the discussion in a perfect framework (outline); and study the verses. Data collection techniques using observation, interview, and documentation. The results of this study indicate that the existence of understanding the verses of the Qur’an for students of campus 2 IAIN Sultan Amai Gorontalo as a guide and influence on daily life. However, there are also students who are not influenced by the Qur’an, encounter obstacles so that they are not affected by the existence of the Qur’an because they only study without understanding and applying it in life, because they are still affected by the environment and have not been able to control their passions, and the solution is with a strong faith, always muh}asabah and raise awareness in yourself that the Qur’an is the best guide for life.